A class-E amplifier for a loosely coupled inductive power transfer system with multiple receivers - Sutor, Alexander; Heining, Martin; Buchholz, Rainer (Energies, 2019)
We present a method for optimizing the electronic power system for a new type of photobioreactor or photoreactor in general. In the case of photobioreactors, photosynthetic active microorganisms or cells are grown. A novel concept for the illumination of photobioreactors was necessary, as the external illumination of those reactors leads to a limited penetration depth of light. Due to the limited penetration depth, no standard reactors can be use for cultivation, but custom made reactors with very small volume to surface ratio have to be used. This still prevents the technology from a large scale industrial impact. The solution we propose in this paper is an internal illumination via Wireless Light Emitters. This increases the manageable culture volume of photosynthetic active microorganisms or cells. The illumination system is based on floating light emitters, which are powered wirelessly by near field resonant inductive coupling. The floating light emitters are able to illuminate a photobioreactor more homogeneously than external illumination systems do. We designed a class-E amplifier and field coils to produce an intermediate frequency electromagnetic field inside the reactor. An appropriate magnetic flux density was found to be approx. B = 1mT and the driving frequency is f = 176 kHz. We conducted experiments with a laboratory size photoreactor. The cultivation volume was 30 L containing up to 3000 WLEs. The maximum electric power input was more than 300W and we calculated an efficiency of up to 76%.
CRIS-Team Scopus Importer:2019-05-07
Keywords: Class-E amplifier; Photobioreactor; Wireless light emitter; Wireless power transfer

A Method for Optimizing the Field Coils of Internally Illuminated Photobioreactors - Sutor, Alexander; Heining, Martin; Lindenberger, Christoph; Buchholz, Rainer (Proceedings of INTERMAG2014, 2014)

Application of light-emitting diodes (LEDs) in cultivation of phototrophic microalgae: current state and perspectives - Becker, Anna; Glemser, M.; Heining, Martin; Schmidt, J.; Becker, A.; Garbe, Daniel; Buchholz, Rainer; Brueck, T. (Applied Microbiology and Biotechnology, 2016)
The quality and regulation of the incident light is crucial in microalgae cultivation processes. Depending on wavelength, spectrum, and intensity, growth characteristics and biochemical composition of these organisms vary. With mainly fluorescent lamps (FL) used previously for illumination, such variabilities could not be studied adequately due to their broad emission spectrum. In contrast, light-emitting diodes (LEDs) emit a very narrow wavelength band and enable flexible photobioreactor designs due to their small size. This review provides a condensed overview on the application of LEDs in microalgal cultivation processes. It summarizes the current availability and applicability of LED technologies as an illumination source for research-focused photobioreactor systems. A particular focus is the use of narrow-wavelength LEDs to address fundamental as well as applied aspects of light color on algae biomass and value-added compound formation. In this respect, the application of internal and external illumination systems is reviewed together with trends in the industrial use of LED systems to intensify algae process efficiency.
Keywords: LED; Light-emitting diodes; Microalgae; Photobioreactor; Wavelengths

Cultivation of phototrophic microorganisms in photobioreactors illuminated via Wireless Light Emitter - Heining, Martin; Sutor, Alexander; Lindenberger, Christoph; Stute, Stephanie; Buchholz, Rainer (10th European Symposium on Biochemical Engineering Sciences and 6th International Forum on Industrial Bioprocesses, 2014)

Internal Illumination of photobioreactors via Wireless Light Emitter – a proof of concept - Heining, Martin; Sutor, Alexander; Lindenberger, Christoph; Stute, Stephanie; Buchholz, Rainer (Young Algaeneers Symposium, 2014)

Internal illumination of photobioreactors via wireless light emitters: a proof of concept - Heining, Martin; Sutor, Alexander; Stute, Stephanie; Lindenberger, Christoph; Buchholz, Rainer; Buchholz, Rainer (Journal of Applied Phycology, 2015)
A novel concept for internal illumination of photobioreactors via wireless light emitters (WLEs) has been developed to increase the manageable culture volume of photosynthetic active microorganisms or cells. The illumination system is based on free suspendable light emitters, which are powered wirelessly by near-field resonant inductive coupling and, therefore, are able to illuminate a photobioreactor more homogeneously than external illumination systems. Since an intermediate frequency electromagnetic field (IF-EMF) acts inside the reactor, the impact of an IF-EMF (B = 0.95 mT, f = 178 kHz) on the green alga Chlamydomonas reinhardtii is determined. The growth rate, the achieved cell dry weight, and the maximum photosynthetic yield Y (0) are unaffected by the applied IF-EMF. Furthermore, a negative effect of the potentially occurring mechanical stress due to the suspended WLE can be excluded. A culture which is mechanically stressed by 125 WLEs per liter shows the same maximal growth rate of 2.29 day(-1) as a control culture. Finally, the comparison of an externally illuminated photobioreactor and a via WLE internally illuminated photobioreactor shows the same growth rates in the exponential growth phase. However, the growth rate in the linear phase is more than twice the rate of the externally illuminated control culture, resulting in a more than 80 % higher achieved biomass. Light profiles over the cross section of both reactor types show clearly that the internal illumination via WLE results in a more uniform light distribution and a higher average light intensity in the reactor.
Keywords: Photobioreactor; Internal illumination; Wireless light emitter; Magnetic field; Wireless energy transfer; Near-field resonant inductive coupling

Licht ins Grüne - Glemser, Matthias; Schmidt, Johannes; Heining, Martin; Becker, Anna; Arnold, Oliver; Garbe, Daniel; Buchholz, Rainer; Brueck, Thomas (2015)
UnivIS-Import:2017-12-18:Pub.2015.tech.ITC.cbiove.lichti

Method for Optimizing the Field Coils of Internally Illuminated Photobioreactors - Sutor, Alexander; Heining, Martin; Lindenberger, Christoph; Buchholz, Rainer (IEEE Transactions on Magnetics, 2014)
We present a method for optimizing the design of field coils for a new type of photobioreactor (PBR). In those PBRs, photosynthetic active microorganisms or cells are grown. A novel concept for the illumination of PBRs was necessary, as the external illumination of those reactors leads to a limited penetration depth of light. The solution we propose is an internal illumination via wireless light emitters (WLEs). This increases the manageable culture volume of photosynthetic active microorganisms or cells. The illumination system is based on floating light emitters, which are powered wirelessly by near field resonant inductive coupling. The floating light emitters are able to illuminate a PBR more homogeneously than external illumination systems. We designed field coils to produce an intermediate frequency electromagnetic field inside the reactor. We chose a magnetic flux density B = 0.95 mT and a frequency f = 178 kHz. To reach optimal efficiency, the magnetic field has to be as homogeneous as possible. We demonstrate how this optimization can be performed with the method of differential evolution. Using the optimized field coil design, the minimum magnetic field was increased by almost 10% keeping the number of ampere-turns constant. A comparison of the light profiles over the cross section of both reactor types show clearly that the internal illumination via WLE results in a more uniform light distribution and a higher average light intensity in the reactor. An impact of the magnetic field on the green alga Chlamydomonas reinhardtii could be excluded by comparing the growth rate, the achieved cell dry weight and the maximum photosynthetic yield with and without applied magnetic field. Furthermore, a negative effect of the potentially occurring mechanical stress due to the suspended WLE can be excluded. A culture which is mechanically stressed by 125 WLE per liter shows the same maximal growth rate as a control culture. Finally, the comparison of an externally and a via WLE internally illuminated PBR shows the same growth rates in the exponential growth phase. However, the growth rate in the linear phase is more than twice the rate of the externally illuminated control culture, resulting in a more than 80% higher achieved biomass.
Keywords: Global optimization; internal illumination; near field resonant inductive coupling; photobioreactor (PBR); wireless energy transfer; wireless light emitter (WLE)

Photobioreactors with internal illumination - A survey and comparison - Buchholz, Rainer; Heining, Martin; Buchholz, Rainer (Biotechnology Journal, 2015)
The idea of internally illuminated photobioreactors has existed since the 1990s and various systems were developed since. Recently, the interest in these systems has been on the rise again, due to the increased production of and research on high-value products and recombinant proteins from microalgae and plant cell cultures. While promising results in lab-scale have been achieved, the potential of photoautotrophic or mixotrophic production of these compounds is limited due to the lack of scalable photobioreactors, which could be overcome by internally illuminated systems. In this article, we review different internally illuminated photobioreactors from the last two decades and classify them into two major groups. The photobioreactors are compared based on the ratio of illuminated surface-to-culture volume and the occupied volume by internal light-emitting elements, and possible obstacles, challenges and future trends are discussed. Looking forward, new technologies and smaller light sources have improved the potential of internally illuminated photobioreactors with internal light sources and will enable these technologies to compete with systems with internal light guides, but only a few of these systems have currently achieved a relevant scale.
UnivIS-Import:2017-07-10:Pub.2015.tech.ITC.cbiove.photob
Keywords: Internal illumination; Light guides; Optical fibers; Photobioreactor; Wireless light emitter

Wireless Light Emitter (WLE) zur internen Beleuchtung von Photoreaktoren - Heining, Martin; Sutor, Alexander; Lindenberger, Christoph; Buchholz, Rainer (Tagungsband, 2013)